Public Attitude Towards Dentists And Dental Services In Ghaziabad City, India (International Journal of Food and Nutritional Sciences, 2022)
Background & Objective: Both dental service providers and planners benefit from an understanding of the public's perception of dentists and dental services. In order to determine how the general public in Ghaziabad, India feels about dentists and dental services, a study was carried out. Methods: A multistage cluster sampling procedure was used to choose 400 people of Ghaziabad. The individuals were given a structured questionnaire that contained statements about the general public's perception of dentists and dental services in Ghaziabad city. A Likert scale with five points was employed to gauge attitude. Results: About 67.8% of the survey participants had been to the dentist at least once in their lives. Waiting times, equipment cleanliness, and dentist advice to patients to stop unhealthy behaviors including smoking, drinking, and pan chewing were all met with negative responses. Positive attitudes were seen about the accessibility of dental services close to one's place of home or employment, the utilization of contemporary medical technology in patient care, and the integrity of dental practitioners. About 67% of study participants thought dental services were pricey. Only 65% of research participants believe routine checkups prevent dental disorders, and 33% think dental care can be put off if there are other costs. Conclusions: The subjects' attitudes toward dentists and dental treatments were largely favorable. The waiting time and hygiene both elicited negative reactions.